Bank reactions after capital shortfalls - Christoffer Kok; Glenn Schepens (National Bank of Belgium, 2013)
This paper investigates whether European banks have capital targets and how deviations from the target impact their equity composition and activity mix. Using quarterly data for a sample of large European banks between 2004 and 2011, we show that there are notable asymmetries in banks' reactions to deviations from optimal capital levels. Banks prefer to reshuffle risk-weighted assets or increase asset holdings when being above their optimal Tier 1 ratio, whereas they rather try to increase equity levels or reshuffle risk-weighted assets without changing asset holdings when being below target. At the same time, focusing instead on a unweighted equity ratio target, we find evidence of deleveraging and lower loan growth for undercapitalized banks during the recent financial crisis, whereas in the pre-crisis periods banks primarily reacted to deviations from their optimal target by adjusting equity levels.
Keywords: D22; E44; G20; G21; G28; 330; Banking; banking capital optimization; financial regulation; deleveraging; capital structure